The Relationship Between Postpartum Mothers' Knowledge of Personal Hygiene and The Healing of Perineal Tears at Romana Clinic, Tanjung Anom Village - Helmi Wardah Nasution; Ferika Desi; Khoirunnisa’a Batubara (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Postpartum perineal wounds are common complications during vaginal delivery that significantly affect maternal health and recovery. The healing process of these wounds is influenced by multiple factors, including the mother's knowledge and practice of personal hygiene. This study aimed to examine the relationship between postpartum mothers' knowledge of personal hygiene and the healing duration of perineal tears at Romana Clinic, Tanjung Anom Village, Pancur Batu Subdistrict, Deli Serdang Regency. A quantitative descriptive-analytic study with a cross-sectional design was employed. A total of 32 postpartum mothers who experienced perineal tears were included using total sampling. Data were collected via a validated structured questionnaire on knowledge and hygiene practices, supplemented by clinical wound healing assessment conducted by qualified midwives on postpartum day 6. Data were analyzed using Fisher's Exact Test, with a significance threshold of p < 0.05. The results indicated that 40.6% of respondents had fair knowledge, 37.5% had poor knowledge, and 21.9% had good knowledge of personal hygiene. Regarding wound healing outcomes, 65.6% of respondents experienced delayed healing (>6 days), while 34.4% achieved wound healing within six days (≤6 days). Statistical analysis revealed a significant association between knowledge of personal hygiene and the healing of perineal tears (p = 0.003), with a large effect size (Cramer's V = 0.60). Respondents with good knowledge demonstrated substantially higher rates of timely wound healing (85.7%) compared to those with fair (30.8%) or poor knowledge (8.3%). Higher levels of knowledge regarding personal hygiene are significantly associated with faster perineal wound healing. These findings underscore the importance of integrating structured hygiene education into routine antenatal and postnatal midwifery services to minimize postpartum complications and promote maternal recovery.Keywords: Maternal Knowledge, Postpartum Mothers, Personal Hygiene, Perineal Wound Healing, Wound Healing Duration.Key